Towards a functional understanding of species coexistence: ecomorphological variation in relation to whole‐organism performance in two sympatric lizards. (27th April 2017) - Žagar, Anamarija; Carretero, Miguel A.; Vrezec, Al; Drašler, Katarina; Kaliontzopoulou, Antigoni
Summary: We examined intra‐ and interspecific variation in functional morphology and whole‐organism performance in a sympatric lizard species pair, Iberolacerta horvathi and Podarcis muralis, in the area with a high potential for competition. The biggest variation between species was found in two functional traits, bite force and climbing speed, linked with corresponding morphological traits. The species with larger and taller heads, P. muralis, exhibited correspondingly stronger bite forces. The other species exhibited smaller and flatter head. Both traits may potentially promote segregation between species in trophic niche (stronger bites relate to harder prey) and in refuge use (flatter heads allow using narrower crevices, hence, influencing escaping from common predators). Stronger bites and larger heads also provide one species with a dominant position in interspecific agonistic interactions. Females had longer trunks that impacted negatively on climbing speed, which may lower anti‐predator escape abilities of the more trunk‐dimorphic species, but positively influence reproductive effort. Our results exemplify how the joint examination of morphological and functional traits of ecologically similar and sympatric species can provide a mechanistic background for understanding their coexistence, namely, syntopic populations that are frequent in the study area. The identified roles of functional morphology in this system of sympatric rock lizards support the contribution of functional diversification for the complexity of community structure via coexistence. A lay summary is available for this article. Abstract : Lay Summary